Penegakan Hukum Terhadap Pelaku Tindak Pidana Pencucian Uang (TPPU) Di Kota Batam - Manurung, Intan; Tan, Winsherly; Sudirman, Lu (Pamulang Law Review, 2025)
The Anti-Money Laundering (AML) program is designed to detect and prevent the flow of illicit funds, particularly those linked to terrorism financing. However, law enforcement efforts face significant challenges, including inadequate coordination in tracking digital transactions, technical limitations, and the complexity of proving criminal acts. These issues are especially pronounced in the Riau Islands Province, Indonesia, which has the highest potential for money laundering due to its strategic border location. Batam City, a key economic hub, ranks second after Jakarta regarding suspicious financial transactions. This study examines the effectiveness of the AML program in addressing money laundering in Batam City. Using an empirical approach, the research analyzes the coordination and implementation of AML initiatives at regional and provincial levels. Findings reveal critical gaps in enforcement strategies and highlight the need for improved interagency collaboration, advanced technical capabilities, and streamlined legal processes to combat money laundering effectively. The study concludes by proposing actionable solutions to reduce the prevalence of suspicious financial activities in Batam City. Key recommendations include strengthening regulatory frameworks, enhancing digital transaction monitoring, and fostering regional cooperation. This research contributes to the broader effort of fortifying Indonesia’s financial security and integrity